Analyzing the Impact of Artificial Intelligence on the Effectiveness of Lecturers’ Teaching Skills - Simorangkir, Melda; Manalu, Risma Uly; Siregar, Edison (Jurnal Evaluasi Pendidikan, 2025)
This study analyzes how lecturers use Artificial Intelligence (AI) in teaching and its effect on teaching effectiveness. The research was conducted at the Christian University of Indonesia (UKI), reflecting the institution’s commitment to quality and innovation in higher education. Using a quantitative approach with multiple linear regression, the study involved 52 purposively selected permanent lecturers from the Faculty of Teacher Training and Education and the Faculty of Vocational Studies, all holding at least the rank of Assistant Professor. Results show that AI usage and the level of AI integration, when combined, significantly affect lecturers' ability to teach using AI (R² = 0.759). However, individually, only the level of integration was statistically significant, while the frequency of AI use was not. These findings suggest the need for more structured and strategic AI integration to improve teaching skills. The study provides important implications for developing policies that enhance lecturers’ technological competencies.